Analyzing The Efficiency Rate of Local Government's Expenditure in Education and Healthcare Sectors Using The Dea Method Towards Human Capital in Madura Between 2020 and 2024 - Muhammad Fauzil Adhim; Zuhriya Octasya Qudsi; Shelo Mustiko Ayu Romantis; Ramadhani Dewi Azzahra; Lovina Rahma Arlitasari; Latifatun Nasekah; Aghnavyra Bhakti Pertiwi; Sulton Fatoni (Jurusan Ilmu Ekonomi Fakultas Ekonomi Universitas Trunojoyo Madura, 2026)
The purpose of this study is to analyze the efficiency of government expenditure in the education and health sectors across four regencies on Madura Island, Bangkalan, Sampang, Pamekasan, and Sumenep, during the 2020–2024 period. This topic is significant because, despite the government's mandate to allocate at least 20% of the budget for education and 5% for health, the Human Development Index (HDI) achievements in Madura remain below the average of East Java Province. This disparity raises a research question: Has regional government spending in the education and health sectors on Madura Island been efficient in improving human development during the 2020–2024 period? The novelty of this study lies in its focus on analyzing inter-regional efficiency among the regencies of Madura using the Data Envelopment Analysis (DEA) approach within the post-pandemic period, which has rarely been examined at the regency level with similar socio-economic characteristics. The research employs a quantitative approach using an input-oriented Variable Return to Scale (VRS) model, with input variables consisting of education expenditure, health expenditure, and GDP per capita, and output variables including Mean Years of Schooling (MYS), Expected Years of Schooling (EYS), and Life Expectancy (LE). Secondary data were obtained from official publications of BPS (Statistics Indonesia) and DJPK (Directorate General of Fiscal Balance) for the years 2020–2024. The results indicate that the level of government spending efficiency varies between districts. Sampang District is the most efficient, with an average score of 0.94, and achieved full efficiency in the 2020–2021 period.In contrast, Sumenep District has the lowest efficiency, with a score of 0.82. Bangkalan and Pamekasan showed fluctuating efficiency, with Pamekasan reaching increasing returns to scale in 2022–2023. This study concludes that managerial capacity and budget scale significantly influence Madura Island's fiscal efficiency, which is currently not optimal. The implication is that there is a need to improve budget management, equalize infrastructure, and optimize the scale of public spending so that regional expenditure is more effective in promoting improvements in HDI. Keywords: Fiscal Efficiency, Local Government’s Expenditure, and HDI